A shift in the conceptual understanding of physics students in Indonesia through the wright map - Sukarelawan, Moh. Irma; Puspitasari, Ariati Dina; Sulisworo, Dwi; Kuswanto, Heru; Jumadi, Jumadi (Jurnal Pendidikan dan Pengajaran, 2022)
There is limited literature reporting on the use of the Rasch model in analyzing the conceptual understanding of student temperature in Indonesia. This study aims to analyze students’ conceptual understanding using a two-level diagnostic instrument. Students’ conceptual understanding was administered through a survey method using a two-level misconception diagnostic instrument. The survey was conducted on 26 students (31% boys and 69% girls) at a public high school in the Tidore Islands, Indonesia. Students’ conceptual understanding of the temperature material was administered using six diagnostic items and analyzed using the Wright map. The analysis results showed a shift in the level of conceptual understanding of 50% of students. So, the Wright map provides a visualization of shifts in the level of students’ conceptual understanding of the topic of temperature.